Transcatheter Closure of a Ragged Post-Myocardial Infarction Ventricular Septal Defect Using an Off-Label ASD Occluder - Quast, Christine; Afzal, Shazia; Leuders, Pia; Masyuk, Maryna; Klein, Kathrin; Kelm, Malte; Polzin, Amin; Zeus, Tobias (Archives of Clinical and Medical Case Reports, 2022)
Post-myocardial infarction ventricular septal defect has become a rare event following ST Elevation Myocardial Infarction (STEMI) but is still a life-threatening complication with high mortality. Transcatheter closure of post-myocardial infarction ventricular septal defects has emerged as an alternative therapeutic approach but often requires individual strategies due to complex morphology. We report a case of a 62-year-old man who was admitted to our hospital after STEMI of the inferior wall with pulmonary congestion due to a post-myocardial infarction VSD for interdisciplinary evaluation and therapy. The patient was characterized by estimated high perioperative risk and underwent interventional closure of the VSD according to heart team decision. Because of ragged nature of the VSD closure with a conventional Occlutech™ VSD occluder was not possible. Therefore, we decided to close the defect using an off-lable device for ASD closure which was successfully implanted without relevant residual shunt.